A Rat Model of Cocaine-Alcohol Polysubstance Use Reveals Altered Cocaine Seeking and Glutamate Levels in the Nucleus Accumbens - Stennett, Bethany A.; Knackstedt, Lori A. (Frontiers in Neuroscience, 2020)
Preclinical models of cocaine use disorder are widely utilized to identify neuroadaptations underlying cocaine seeking and to screen medications to reduce seeking. However, while the majority of cocaine users engage in poly-substance use (PSU), a minority of preclinical studies employ PSU models. We previously reported that when rats consume alcohol after daily intravenous cocaine self-administration, nucleus accumbens (NA) core basal glutamate levels are reduced below those of rats that consumed only cocaine, and do not increase during cue+cocaine-primed reinstatement of cocaine-seeking. Here we used the same model of sequential cocaine and alcohol self-administration to test the hypothesis that a similar pattern of glutamate changes would be observed in the NA core prior to and during a cocaine-primed reinstatement test. Rats underwent intravenous cocaine self-administration followed by access to unsweetened alcohol in the home cage for 12 days. Rats underwent a minimum of 12 daily extinction sessions prior to a cocaine-primed reinstatement test conducted during microdialysis procedures. Contrary to our previous work using the same model, here we found that access to alcohol increased cocaine intake and increased responding during early extinction training. We found that as in our previous work, cocaine+alcohol-consuming rats displayed basal glutamate levels below those of rats that self-administered only cocaine. During the cocaine-primed reinstatement test, rats that consumed only cocaine displayed increased glutamate efflux in the NA core while those that consumed cocaine+alcohol did not. These results indicate that preclinical models of PSU should be utilized to develop experimental therapeutics for the reduction of cocaine seeking.